2019
DOI: 10.7861/clinmedicine.19-4-299
|View full text |Cite
|
Sign up to set email alerts
|

Nausea and vomiting in palliative care

Abstract: Table 1 outlines common causes and examples of N&V. It should be noted that many patients in this study had more than a single cause for their N&V. Nausea and vomiting in palliative care are commonly experienced symptoms, and the aetiology is often multifactorial. The most common causes are impaired gastric emptying, chemical causes (eg medication) and visceral causes (eg constipation). Close attention should be paid to the clinical features which may suggest the likely cause. Antiemetic therapy should be guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
3
7
0
4
Order By: Relevance
“…The results of this study also showed that the likelihood of developing psychosocial distress was higher among cancer patients with severe nausea when compared to patients with no severe nausea. This result was consistent with ndings from other studies (79). This could be due to the fact that nausea is still a serious side effect of cancer therapy, frequently resulting in dramatic changes in the patient's emotions, social activities, and work situations.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study also showed that the likelihood of developing psychosocial distress was higher among cancer patients with severe nausea when compared to patients with no severe nausea. This result was consistent with ndings from other studies (79). This could be due to the fact that nausea is still a serious side effect of cancer therapy, frequently resulting in dramatic changes in the patient's emotions, social activities, and work situations.…”
Section: Discussionsupporting
confidence: 92%
“…There were also significant variations in their use across different services depending on their jurisdiction. Antiemetics followed by opioids and benzodiazepines were found to be the highest prescribed AM (Leach, 2019). This is somewhat different from other studies where opioids were considered the main AM prescribed for end-of-life care (Khalil et al, 2019) but consistent with other studies by Bowers et al (2019) where midazolam and opioids were cited as the most prescribed drugs.…”
Section: Main Findingssupporting
confidence: 48%
“…The collection of side effects commonly observed while using VR has been labelled “cybersickness” and is generally reported to consist of symptoms including nausea, dizziness, disorientation, light-headedness, and headaches [ 19 , 20 ]. The prevalence of nausea in palliative care cancer patients has been reported as high as 68% [ 21 ]. Therefore, greater care must be taken when using VR with palliative care patients so as not to exacerbate any existing symptoms.…”
Section: Introductionmentioning
confidence: 99%